Analisis Struktural Dan Kearifan Lokal Dalam Legenda “Terjadinya Mado-Mado Nias” Dari Etnis Nias Dan Legenda “Turi-Turin Si Belu Tole” Dari Etnis Karo Serta Relevansinya Dengan Pembelajaran Bahasa Indonesia - Roita Sinaga; Emasta Evayanti Simanjuntak (FKIP, Universitas Palangka Raya, 2023)
The purpose of this research is to analyze the structure and local wisdom in legends in one of the tribes in North Sumatra. The purpose of this study is to analyze the legends of the nias and karo tribes. The method used in this research is descriptive qualitative. The sources of data used in this research are journals, books, and internet sites related to the topics that have been selected. Structural studies include: theme, plot, setting, characters and characterizations, style of language, and point of view. The types of local wisdom include: Welfare and peace. In the legend